2015
DOI: 10.4103/2229-3485.159941
|View full text |Cite
|
Sign up to set email alerts
|

Consent for audio-video recording of informed consent process in rural South India

Abstract: Introduction and Objectives:In recent times, audio-video (A-V) recording of consent process for all the study subjects entering a clinical trial has been made mandatory. A-V recording of informed consent process is a big challenge due to confidentiality and the sociocultural environment in India. It is important to find out the acceptability for A-V recording of the consent process and reasons for refusal, if any to address this new challenge.Materials and Methods:A descriptive survey was done among 150 reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(4 reference statements)
1
8
0
Order By: Relevance
“…AV recording of informed consent discussions : acceptability of and support for AV recordings varied (a third of lay participants refused in a hypothetical study and nearly all agreed in a real vaccine trial 72 83 ; a third to two-thirds of investigators were in support. 79 89 133 Concerns included the increase in time/resources required to carry out AV recordings and the lack of adequate guidance and support.…”
Section: Resultsmentioning
confidence: 99%
“…AV recording of informed consent discussions : acceptability of and support for AV recordings varied (a third of lay participants refused in a hypothetical study and nearly all agreed in a real vaccine trial 72 83 ; a third to two-thirds of investigators were in support. 79 89 133 Concerns included the increase in time/resources required to carry out AV recordings and the lack of adequate guidance and support.…”
Section: Resultsmentioning
confidence: 99%
“…The Quintet Recruitment Intervention recommends recording conversations between recruiters and potential participants to learn more about the recruitment conversation and how that conversation could be improved [22]. However, it should be noted that requests to record these conversations have sometimes been rejected by a substantial minority of potential trial participants [23].…”
Section: Discussionmentioning
confidence: 99%
“…A study among rural community regarding their willingness to be recorded during the consent process found that more than one-third of the participants refused to be videotaped due to lack of interest in AV recording or feeling shy in front of the camera. [ 4 ] The rule was further amended in 2015, where it was clarified that AV recording was mandatory only for vulnerable participants in NCE trials. Further, only audio recording needs to be maintained of the informed consent process in case of anti-HIV or antileprosy drug trials.…”
Section: Methodsmentioning
confidence: 99%